On the named Wrongful Acts - Espinoza Espinoza, Juan (2015)
This article addresses the topic of civil wrongful acts that can cause tort liability. The author criticize the position that holds that wrongfulness is not an element of tort liability. In accordance with that position, not considering wrongfulness as an element of tort liability, it permits to consider that some “lawful acts” could cause tort liability. On the contrary, Espinoza consider those supposed “lawful acts” as examples of abuse of law so they are actually wrongful acts.